Single versus multiple-family intervention in childhood overweight - Finnmark Activity School: A randomised trial - Kokkvoll, Ane Sofie; Grimsgaard, Sameline; Ødegård, Rønnaug; Flægstad, Trond; Njølstad, Inger (Archives of Disease in Childhood, 2014)
This article is part of Anne Sofie Kokkvoll's doctoral thesis, which is available in munin at http:// hdl.handle.net/10037/6964